Integrated Analysis of Osmotic Stress and Infrared Thermal Imaging for the Selection of Resilient Rice Under Water Scarcity - Mahreen, Naima; Yasmin, Sumera; Asif, M.; Yousaf, Sumaira; Yahya, Mahreen; Ejaz, Khansa; Shahid Hussain, Hafiz; Sajjid, Zahid Iqbal; Arif, Muhammad (Frontiers in Plant Science, 2022)
Climate change scenario has increased the severity and frequency of drought stress, which limits growth and yield of rice worldwide. There is a dire need to select drought tolerant rice variety to sustain crop production under water scarcity. Therefore, the present study effectively combined morpho-physiological and biochemical approaches with high throughput technology of infrared thermal imaging (IRTI) for reliable selection of drought tolerant genotypes. Initially, we studied 28 rice genotypes including 26 advance lines and 3 varieties for water stress tolerance under net house conditions. Three genotypes NIBGE-DT-02, KSK-133 and NIBGE-DT-11 were selected based on Standard Evaluation System (SES) scoring for drought tolerance. NIBGE-DT-02 showed tolerance to polyethylene glycol (20%) induced osmotic stress indicated by minimum reduction in seedling length, biomass, chlorophyll content and increased leaf proline content as compared to susceptible variety under hydroponic system. NIBGE-DT-02 was further evaluated for water withholding at varying growth stages i.e., 30 and 60 days after transplantation (DAT) in pots under net house conditions. NIBGE-DT-02 showed significantly least reduction (35.9%) in yield as compared to susceptible variety (78.06%) under water stress at 60 DAT with concomitant induction of antioxidant enzymes such as peroxidase, catalase and polyphenol oxidase. Significant increase (45.9%) in proline content, least increase (7.5%) in plant temperature along with least reduction in relative water content (RWC; 5.5%) and membrane stability index (MSI; 9%) were observed under water stress at 60 DAT as compared to well-watered control. Pearson correlation analysis showed strong correlation of shoot length with MSI and root length with RWC in rice genotypes at later growth stage. Furthermore, Regression analysis indicated negative correlation between plant temperature of NIBGE-DT-02 and proline, RWC, MSI and peroxidase enzyme under variable water stress conditions. All these responses collectively validated the adaptive response of selected genotype under water stress during different growth stages. Tolerant genotype can be used in breeding programs aimed at improving drought tolerance and can expand rice cultivation. Furthermore, this study provides foundation for future research directed to utilize IRTI as a fast and non-destructive approach for selection of potent rice genotypes better adapted to water scarcity from wide germplasm collection.